(untitled) (Politeja, 2025)
DISCURSIVE PRACTICES AND THE PROCESS OF CONSTRUCTING POLITICAL REALITY. IN SEARCH OF THE POSSIBILITY OF DIALECTICAL EXPLANATION The article’s starting point is the anti-naturalist assumption that the social world is socially constructed. The conceptualisation of the social reality’s susceptibility to change through the discourse assumes that 1) texts/statements are part of a dialectical process in which a kind of “materialization” of meanings takes place, while 2) contextual factors condition ways of perceiving reality. The analysis aims to trace the possibilities and limitations of scientific cognition within such an outlined research field.